2010
DOI: 10.3923/ijss.2010.112.130
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Soil Properties of Lowland and Hill Dipterocarp Forests at Peninsular Malaysia

Abstract: A study was conducted to characterize soil properties of a rehabilitated-degraded forestland and an adjacent natural forest in two major forest types, representing the lowland and hilldipterocarp forests at Bidor and Kinta Forest Reserves, respectively. Twelve soil profiles were dug at both sites. At Bidor site, the soil profiles were under rehabilitated secondaiy forests (B1 and B2), an abandoned Acacia mangium plantation (B3 and B4) and natural forests (B5 and B6) of lowland dipterocarp. However, at Kinta si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
1
27
0
1
Order By: Relevance
“…The Al concentrations and organic matter influenced the soil acidity. According to Zaidey et al (2010) the increase of pH with increasing depth may be related to the contents of Fe and Al oxides, while the content of organic matter exhibit high and low pH values. Soil organic matter was restored after 8 years of planting (Carlos et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Al concentrations and organic matter influenced the soil acidity. According to Zaidey et al (2010) the increase of pH with increasing depth may be related to the contents of Fe and Al oxides, while the content of organic matter exhibit high and low pH values. Soil organic matter was restored after 8 years of planting (Carlos et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have been conducted to characterize the soil properties in Malaysia (Ishizuka et al, 2000;Hattori et al, 2005;Abdu et al, 2007;Zaidey et al, 2010), a crucial information in relation to physical and chemical properties under rehabilitation of degraded forest land with various dipterocarp species is rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…The pH for both surface and subsurface soils in secondary forest was more acidic than those in the rehabilitation forest, which were associated with high exchangeable Al. The acidity occurring in the forest soils was due to the presence of Al and H. According to Zaidey et al (2010), the Al concentrations and organic matter influenced the soil acidity. Moreover, the acidity may be caused by water deficiency due to drought (Akbar et al, 2010).…”
Section: Ajesmentioning
confidence: 99%
“…Parfitt et al (1995) also reported that lower contents of clay and loam in the soil lead to a low CEC values. Other researchers also found that the CEC of soils in tropics were affected by different negative charges derived from clay minerals and due to the amount of clay in soil (Ohta and Effendi, 1992;Hamzah et al, 2009;Saga et al, 2010;Zaidey et al, 2010;Sakurai et al, 1998;Arifin et al, 2008;Roslan et al, 2011). Total N and total C were also low and hence these soils are considered as very poor.…”
Section: Initial Properties Of the Soilmentioning
confidence: 99%